Cape Verde : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper analyzes economic developments in Cape Verde during 1990-99. Although the GDP growth rates accelerated, unemployment remained at the high level of about 25 percent and fiscal policies, until 1996, unsustainably lax. This situation resulted in the rapid accumulation of domestic debt and the depletion of foreign reserves to a level as low as half a month of imports in early 1996. Largely as a result of fiscal contraction and droughts, growth rates of real GDP during 1996-98 seemed to have slowed down to some extent.